Factors of Production Influencing Gross Domestic Product in Nepal - Jha, Prabhat; Chandra Dhakal, Shiva (Nepal Journal of Science and Technology, 2021)
This study has analysed the factors of production, viz; agricultural land, working force and gross fixed capital formation (GFCF) of Nepal between 2000/01-2017/18 AD and has determined their effects on national income, viz; Gross Domestic Product (GDP) by using Cobb-Douglas regression function. The results showed an average growth rate of GDP, agricultural land, working force and GFCF to be 3.9%, 0.8%, 1.5% and 7.9%, respectively, with the values plummeting in 2015/16, due to occurrence of the devastating earthquake in 2015, but then again variable values skyrocketed following years. The regression analysis found that GDP was affected significantly by agricultural land and working force, but insignificant with GFCF. On an average, with the increase in agricultural land and working force by 1 %, GDP increased by 1.1% and 1.7%, respectively. Thus, policy regarding an increment of agricultural land use and employment of labour force must be framed to improve the Nepalese economy.